Pelatihan Pengelolaan Sampah Rumah Tangga Berbasis Komposter Dan Lubang Biopori Di Desa Toto Selatan - Yuniarti Koniyo; Mita Alvionita; Muh. Alsere Bardian Sahaba; Muhammad Rizq Gobel (Jurusan Pendidikan Teknik Elektro, 2026)
Household waste management in South Toto Village, Tilongkabila District, Bone Bolango Regency, remains a pressing environmental issue that requires concrete and sustainable solutions. Most residents have not implemented waste sorting and tend to dispose of or burn waste without proper management, resulting in negative impacts on health and the environment. This community service activity aimed to empower residents through organic waste management training using appropriate technology, namely composting bags and biopore holes as simple, affordable, and environmentally friendly solutions. The implementation method consisted of four stages: (1) preparation and field coordination; (2) counseling; (3) practical training; and (4) monitoring and evaluation. The activity was carried out participatorily involving 20 participants from various community groups, including housewives, youth organizations, and community leaders. The results showed significant improvements in participants’ knowledge, skills, and awareness of the importance of sustainable household waste management. Most participants were able to independently manage organic waste, produce compost for yard plants, and implement biopore holes to improve soil water absorption. The activity also encouraged the formation of environmental action groups at the neighborhood level and plans to establish a Waste Bank in South Toto Village as a program sustainability measure. Thus, this activity successfully fostered community participation and independence in maintaining environmental cleanliness based on local empowerment.